Pre-service EFL Teacher Cognition: Learning to Teach English through Authentic Materials - Dilan Ökcü; Hatime Çiftçi (Sakarya University Journal of Education)
Themain purpose of this study is to investigate how pre-service EFL teachersconstruct their knowledge and understanding while learning to teach through theuse of authentic materials over a 5-week training program. The methodologyinvolved a case study design with one Tanzanian and three Turkish pre-serviceEFL teachers at Department of English Language Teaching (ELT) of a privateuniversity in the northwest of Turkey. Drawing on qualitative research, thestudy utilized various data sources including focus group interviews,reflection papers, in-class discussions, diaries, and observation notes. Theanalysis revealed four major themes that appear to have an influence on theparticipants’ construction of knowledge and understanding in learning to teachEnglish through authentic materials: the role of micro-teaching, the role oftraining, L2 learning experiences, and access to real life. The studydemonstrated that the process of pre-service teachers’ cognition of learning toteach through authentic materials is complex and several factors are in order.